Permutation tests - Zhou, YanYan (Henry Stewart Talks, 2007)
What is a permutation test?, Usual test procedure, What is different about permutation tests?, Choice of test statistics, Generating the data, Assessing the significance, Sample size calculations, Tests based on permutation, Fisher exact test/lady tea tasting, Pros and cons of permutation tests
Archived at 2018/05/31